First two bilateral hand transplantations in India (Part 4): Immediate post-operative care, immunosuppression protocol and monitoring - Iyer, Subramania; Sharma, Mohit; Kishore, P.; Mathew, Jimmy; Janarthanan, R.; Reddy, Raghuveer; Wakure, Abhijeet; Vijayaraghavan, Sundeep; Mali, S. M. Chetan; Varma, Visakh; Chaudhari, Ashish; Dhake, Swapnil; Omkumar, Akshay; Kurian, George; Nair, Rajesh; Mathew, Anil; Paul, Zachariah; Eapen, Malini; Biswas, Lalitha (Indian Journal of Plastic Surgery, 2017)
Introduction: Being able to counter immune-mediated rejection has for decades been the single largest obstacle for the progress of vascular composite allotransplantation (VCA). The human immune system performs the key role of differentiating the ‘self’ from the ‘non-self’. This, although is quintessential to eliminate or resist infections, also resists the acceptance of an allograft which it promptly recognises as ‘non-self’. Materials and Methods: Pre-operative evaluation of the recipient evaluation included immunological assessment in the form of panel reactive antibodies (PRA), human leucocyte antigen (HLA) typing, donor-specific antibody detection assays (DSA) and complement-dependent cytotoxicity assays (CDC). Induction immunosuppression was by thymoglobulin and the maintenance by the standard triple-drug therapy. Results: Both the recipients were managed by the standard triple drug therapy and have had only minor episodes of rejections thus far which have been managed appropriately. Discussion: Induction immunosuppression was by thymoglobulin and the maintenance by the standard triple-drug therapy. Various groups have tried various other formulations and regimes as well. Conclusion: A comprehensive plan has to be drawn up for immunological screening, selection and the post-operative immunosuppressant usage. The ultimate goal of these immunosuppression modalities is to achieve a state of donor-specific tolerance.
Keywords: Composite tissue allotransplantation; hand transplantation; immunosuppression; vascular composite allotransplantation